A quantitative study on the effects of external geomagnetic fields by using the GeoMagSphere back-tracing code. Issue 7 (1st October 2021) - Boschini, Matteo J.; Della Torre, Stefano; Gervasi, Massimo; Grandi, Davide; La Vacca, Giuseppe; Rancoita, Pier Giorgio; Rozza, Davide; Tacconi, Mauro
Abstract: Evaluation of cosmic ray trajectories and penetration inside the Earth environment is mandatory for estimation of flux by on-orbit detectors as well as of radiation damage on electronics devices and biological tissues, like those of astronauts onboard the International Space Station. We studied the impact of the external magnetic field on the calculation of some parameters like the rigidity cut-off, by a quantitative comparison among several geomagnetic field models. For this purpose we used GeoMagSphere back-tracing code, performing the particle trajectory reconstruction back-in-time from the chosen position and time up to the borders of the magnetosphere. The analysis done points out the need to combine an external magnetic field model with the internal one (usually IGRF). Several external field models have a different impact on the accuracy as well as on the time needed for calculation, important in case of a large amount of back-traced particles. We also studied cosmic ray propagation inside the magnetosphere, separately for quiet and disturbed solar activity periods. We found that during highly disturbed periods and during magnetic storms, rigidity cut-off, as well as cosmic ray flux, can be appropriately evaluated only by using external field models, like that one proposed by Tsyganenko and Sitnov (2005), well describing those particular conditions.